MANAGEMENT OF WEEKEND MADRASAH IN DAVAO REGION, PHILIPPINES(Strategies in Establishing Alignment of Weekend Madrasah to DepEd Order No. 41,series of 2017) - Saprolla Rollie Cale Deporos, - (2022)
The research analysed the performance of weekend madrasah education in Davao Region in terms of its total implementation from its general management, students' performance and situations, curriculum development, educational facilities, educational evaluation, teachers, financial matter and legalities that led the weekend madrasah to be underdeveloped and unsupported by the national government level. Educational Management and Administration are the primary topics of the research as the basis of the weekend madrasah development. Through the WMIP or Weekend Madrasah Implementation Program Model as one of the researcher's recommendations to improve the operation of the weekend madrasah and to solidify the connection between the government through DepEd and Weekend Madrasah which is understood as traditional madrasah program. Without compromising their creed and principles as Muslims. Descriptive qualitative method is used in the study. Generally, the data were taken from Regional Offices, Regional Directors, Division Offices, EPS or Educational Program Specialist office and Staff, School Heads, Principals, Teachers or Asatidh of both fields in Public and Private Madrasah. The Department of Education and Madrasah offices. Through documents guide, interview and observation were used as parts of the instruments to meet the main objective of the study, guided by the research questions. The result of the study is very significant because it shows the deficiencies implicating its weaknesses and insufficiencies affecting the low development and infectivity of madrasah implementation, and channelling the ideal resolution to improve the operational implementation and standardization that parallel to DepEd and Weekend Madrasah's Religious principles. The poor academic performance of both madrasah and students, teachers' low capacity in pedagogical knowledge, poor facilities that result to low performing madrasah, no standard curriculum followed, are some of the causes that led them unsupported educational program by the national government level in terms of support force academically, manpower, capacity building, subsidies and other related provisions as how MADARIS and ALIVE program operational aid have. The research proposed the model, named 'The Innovative Model of WMIP: Weekend Madrasah Implementation Program in Davao Region, Philippines', as a recommendation to resolve as an additional solution towards the existing circumstances faced. One of the study's resolutions aside from the WMIP model is to adapt the current government program through DepEd Order No. 41, series of 2017 programmed by the government through the Department of Education's initiative, to have a centralized madrasah education system in the Philippines in corresponding improvement with K-12 curriculum. This is to empower the weekend madrasah, to elevate the capacity of teachers or asatidhs to serve more to their students and make the weekend madrasah quality without sacrificing the Islamic belief and creed, however to improve the pedagogical capacity and managerial knowledge to reach its ideal development.